Water Management Program in Telkom University: Planning and Best Practice - Erna Sri Sugesti; Aris Hartaman; Taufan Umbara (Journal of Sustainability Perspectives, 2023)
This paper discusses the water management conducted by Telkom University, including the fundamental considerations to be taken into account, the implementing organization, the design methods for rainwater systems, and practical experiences in constructing Rainwater Harvesting systems. The management is aware of the conditions and situations related to clean water users, estimates of clean water requirements, potential water sources, and the campus environmental situation. Based on various studies and supported by rainfall data from the Meteorology, Climatology, and Geophysics Agency, a simple calculation was used to derive the design of the Rainwater Harvesting system, which was subsequently implemented. There are several lessons learned from this implementation, including the need for improvements in the foundation structure of soak pits, recommending the construction of ground tanks during the dry season, and the flexibility of ground tank size depending on the availability of funds The abstract should state briefly the purpose of the research, the principal results and major conclusions.